DOZ047.101: Preclinical studies of tissue engineering for long-gap esophageal atresia in pigs. A systematic literature review. (24th June 2019) - Garrido, M; Phylactopoulos, D-E; De Coppi, P; Bonfanti, P
Abstract: Introduction: Current approaches for esophageal substitution in long-gap esophageal atresia (LGEA) are associated with complications that impact quality of life. Tissue-engineered (TE) esophagus appears as a promise to overcome these issues. The pig has been used as large-animal model to test TE esophagus before its clinical application. Different approaches have been reported. This study aims at conducting a systematic review of TE approaches for complete esophageal defects in pigs. Materials and Methods: This work was registered in PROSPERO (ID 127838). A systematic literature review was performed following SYRCLE's guidelines, using the CAMARADES-NC3Rs platform (SyRF). PubMed and OpenGrey databases were reviewed identifying articles on complete esophagus defects in pigs restored by TE. The analyses of bias and 3Rs were based on the ARRIVE guidelines. Results: In the period 2009–2018, 14 articles were identified using pigs as a model for a TE approach in complete esophageal defects. Animal age/weight/sex, size/localization of the defect, TE strategy, follow-up, and outcomes greatly differ among different studies. Few studies report strategies to improve 3Rs and internal validation. Discussion: Further studies in LGEA preclinical models should be performed in an attempt to create a defect in the intrathoracic esophagus. Methodological design may help to avoid bias and define strategies related to the 3Rs. TE approaches with best results include the use of different cell populations seeded in scaffolds that are maturated in bioreactors before their implantation. The next questions to be addressed are developing techniques to avoid stent migration and promoting regeneration of the enteric nervous system.